[Ir(PPh3)2(H)2(ClCH2CH2Cl)][BArF4]: a well characterised transition metal dichloroethane complex. - Moxham, G; Brayshaw, S; Weller, A (2007)
Reaction of [Ir(PPh(3))(2)(COD)][BAr(F)(4)] with H(2) in dichloroethane solution results in [Ir(PPh(3))(2)(H)(2)(ClCH(2)CH(2)Cl)][BAr(F)(4)], which has been fully characterised by X-ray crystallography, NMR spectroscopy and ESI-MS. Its activity towards alkene hydrogenation has been compared with analogous CH(2)Cl(2) complexes.